An Overview of the Crystallized Structures of the SARS-CoV-2 - Ionescu, Mihaela Ileana (Protein J, 2020)
Many research teams all over the world focus their research on the SARS-CoV-2, the new coronavirus that causes the so-called COVID-19 disease. Most of the studies identify the main protease or 3C-like protease (M(pro)/3CL(pro)) as a valid target for large-spectrum inhibitors. Also, the interaction of the human receptor angiotensin-converting enzyme 2 (ACE2) with the viral surface glycoprotein (S) is studied in depth. Structural studies tried to identify the residues responsible for enhancement/weaken virus-ACE2 interactions or the cross-reactivity of the neutralizing antibodies. Although the understanding of the immune system and the hyper-inflammatory process in COVID-19 are crucial for managing the immediate and the long-term consequences of the disease, not many X-ray/NMR/cryo-EM crystals are available. In addition to 3CL(pro), the crystal structures of other nonstructural proteins offer valuable information for elucidating some aspects of the SARS-CoV-2 infection. Thus, the structural analysis of the SARS-CoV-2 is currently mainly focused on three directions—finding M(pro)/3CL(pro) inhibitors, the virus-host cell invasion, and the virus-neutralizing antibody interaction. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10930-020-09933-w) contains supplementary material, which is available to authorized users.